Comparative Quality of Proteins and Morphological Structures of Gelatin From Sheepskin With Acid and Alkaline Treatment - Hasdar, Muhamad; Randi, Mohamamad Jusuf (Universitas Dr Soetomo, 2020)
Sheepskin is one alternative to raw materials for producing gelatin. This study aims to compare the quality of gelatin from sheepskin based on different types of pretreatment solutions used, namely HCl 1,5% solution and NaOH 1,5% solution. Data analysis used t-test to compare two treatment methods. Yield and protein gelatin there is a difference where the treatment of HCl 1,5% solution is higher than the treatment of NaOH 1,5% solution. The brighter visual quality of gelatin colour was produced by HCl 1,5% treatment compared to NaOH 1,5% and commercial gelatin treatments. The results of the microstructure using Scanning Electron Microscopy (SEM) showed that there were still lots of clumps of protein and cavities in the gelatin NaOH 1,5% and commercial gelatin treatments. Gelatin with HCl 1,5% treatment showed the best results.